Toll-Like Receptor 2 as a Regulator of Oral Tolerance in the Gastrointestinal Tract - Tunis, Matthew C.; Marshall, Jean S. (Mediators of Inflammation, 2014)
Food allergy, other adverse immune responses to foods, inflammatory bowel disease, and eosinophilic esophagitis have become increasingly common in the last 30 years. It has been proposed in the “hygiene hypothesis” that dysregulated immune responses to environmental microbial stimuli may modify the balance between tolerance and sensitization in some patients. Of the pattern recognition receptors that respond to microbial signals, toll-like receptors (TLRs) represent the most investigated group. The relationship between allergy and TLR activation is currently at the frontier of immunology research. Although TLR2 is abundant in the mucosal environment, little is known about the complex relationship between bystander TLR2 activation by the commensal microflora and the processing of oral antigens. This review focuses on recent advances in our understanding of the relationship between TLR2 and oral tolerance, with an emphasis on regulatory T cells, eosinophils, B cells, IgA, intestinal regulation, and commensal microbes.